Toward an interdisciplinary field: Language and social interaction research at the University of California, Santa Barbara - Halkowski, Timothy (Hampton Press, Inc., 2010)
Language and social interaction (LSI) has now come of age as a research strand within Communication. This chapter is about a graduate program in LSI whose home is in a sociology department. We begin with a few notes about this situation, before tracing the evolution of LSI scholarship at the University of California, Santa Barbara.
Keywords: Language and social interaction, Conversation analysis, intellectual history, communication, UCSB